The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fenvs.2021.700245
|View full text |Cite
|
Sign up to set email alerts
|

Fate of four Different Classes of Chemicals Under Aerobic and Anaerobic Conditions in Biological Wastewater Treatment

Abstract: The removal mechanisms and extent of degradation of 28 chemicals (triclosan, fifteen polycyclic aromatic hydrocarbons, four estrogens, and eight polybrominated diphenyl ether congeners) in different biological treatment systems [activated sludge, up-flow anaerobic sludge blanket reactor (UASB) and waste stabilization pond (WSP)] was investigated to provide insights into the limits of engineered biological treatment systems. This was done through degradation experiments with inhibition and abiotic controls in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 64 publications
(102 reference statements)
0
2
0
Order By: Relevance
“…This enhancement greatly shortened the debromination period and achieved more extensive debromination of higher BDE-183. The dominantly produced tri-BDEs are less toxic and tend to be more readily degraded by microorganisms in the environment ( ATSDR, 2017 ; Komolafe et al, 2021 ), thus likely reducing the public health risks. Generally, the supplement of the auxiliary substrates of more readily utilized electron acceptors, such as other organohalide pollutants (e.g., trichloroethene) or priming organic nutrients (e.g., lactate) have shown an obvious enhancement of BDE debromination in lab-scale studies ( Robrock et al, 2008 ; Lee and He, 2010 ; Ding et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…This enhancement greatly shortened the debromination period and achieved more extensive debromination of higher BDE-183. The dominantly produced tri-BDEs are less toxic and tend to be more readily degraded by microorganisms in the environment ( ATSDR, 2017 ; Komolafe et al, 2021 ), thus likely reducing the public health risks. Generally, the supplement of the auxiliary substrates of more readily utilized electron acceptors, such as other organohalide pollutants (e.g., trichloroethene) or priming organic nutrients (e.g., lactate) have shown an obvious enhancement of BDE debromination in lab-scale studies ( Robrock et al, 2008 ; Lee and He, 2010 ; Ding et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Conventional WWTP are not designed for the optimal removal of CEC. Recently, studies in the literature analyzed PPCPs in WWTP, based on mass balances and considered their biological or abiotic degradation, presence in liquid phase effluents, or sorption in the sludge sewage [12,13], even focusing on AD of sewage sludge [14]. The analysis of sludge samples from several WWTPs showed that nearly 20 PPCPs can be detected in sewage sludge in concentrations up to 100 ng/g.…”
Section: Introductionmentioning
confidence: 99%